Precompetitive Anxiety and Motivation in Costa Rica Elite Swimmers - Haase, Mikaela (2021)
This study aims to describe the management of precompetitive anxiety in elite Costa Rican swimmers aged 14 to 22 years old, identifying the motivating elements (external and internal) and how the relationship with their coach and their peer group influences the processes of motivation and precompetitive anxiety. Semi-structured interviews were conducted by the end of 2018. The results suggest that among the main elements associated with greater feelings of anxiety are the lack of objectives achieved before the competition, having a poor performance during training, and being aware of the importance of the respective competition. The elite swimmers’ motivations have been classified as intrinsic (Olympic competition, time improvement, placement in rankings) and extrinsic (family, coach, team) ones. Finally, results suggest that a bad relationship with the coach and peer groups could result in a loss of interest in training and competing. In conclusion, when presenting precompetitive anxiety, performance can decrease, causing non-fulfillment of objectives, which leads athletes to demotivate, maintaining anxiety for their next competitions. Keywords: Precompetitive anxiety, Motivation, Swimming, Sport Psychology.